Excavating an extinct Finnic language. Winkler, Eberhard: Krewinisch - Johanna Laakso (Department of European and Comparative Literature and Language Studies, Faculty of Philological and Cultural Studies, University of Vienna) (Finno-Ugrian Society (Suomalais-Ugrilainen Seura), Helsinki, 1999)
The abstract is available here: https://uscholar.univie.ac.at/o:299875 The abstract is available here: https://uscholar.univie.ac.at/o:299875 The abstract is available here: https://uscholar.univie.ac.at/o:299875